Effect of Nano Silica and Ultrafine Fly Ash on Compressive Strength of High Volume Fly Ash Mortar - Supit, S.; Ahmed, Shaikh; Sarker, Prabir (Trans Tech Publications, 2013)
This paper evaluates the effect of Ultrafine Fly Ash (UFFA) and Nano Silica (NS) on compressive strength of high volume fly ash (HVFA) mortar at 7 days and 28 days. Three series of mortar mixes are considered in the first part of this study. In the first series the effect of high content of class F fly ash as partial replacement of cement at 40, 50 and 60% (by wt.) are considered. While in the second and third series, the UFFA and NS are used as partial replacement of cement at 5%, 8%, 10%, 12% and 15% and 1%, 2%, 4%, 6% and 8% (by wt.) of cement, respectively. The UFFA and the NS content which exhibited highest compressive strength in the above series are used in the second part where their effects on the compressive strength of HVFA mortars are evaluated. Results show that the mortar containing 10% UFFA as partial replacement of cement exhibited the highest compressive strength at both 7 and 28 days among all UFFA contents. Similarly, the mortar containing 2% NS as partial replacement of cement exhibited the best performance. Interestingly, the use of UFFA in HVFA mortars did not improve the compressive strength. However, the use of 2% and 4% NS showed improvement in the compressive strength of HVFA mortar containing 40% and 50% fly ash at both ages. The effects of NS and UFFA on the hydration and strength development of HVFA mortar is also evaluated through X-Ray Diffraction (XRD) test. Results also show that the UFFA and NS can significantly reduce the calcium hydroxide (CH) in HVFA mortars.